2022
DOI: 10.20524/aog.2022.0689
|View full text |Cite
|
Sign up to set email alerts
|

Culture-based antibiotic susceptibility testing for Helicobacter pylori infection: a systematic review

Abstract: Background Primary antibiotic resistance in Helicobacter pylori ( H. pylori ) strains is increasing worldwide, affecting therapy success. The use of therapies tailored on susceptibility pre-testing at culture has been proposed, but data are still conflicting. Method We performed a systematic review to evaluate the role of a culture-based therapeutic approach for H. pylori treatment, taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Finally, it has been suggested that more studies were required to demonstrate the theoretical expected superiority of antimicrobial susceptibility testing-guided therapy over empiric therapy [ 24 , 43 ]. However, this goal is difficult to achieve, as these studies are very expensive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it has been suggested that more studies were required to demonstrate the theoretical expected superiority of antimicrobial susceptibility testing-guided therapy over empiric therapy [ 24 , 43 ]. However, this goal is difficult to achieve, as these studies are very expensive.…”
Section: Discussionmentioning
confidence: 99%
“…When antibiotic susceptibility testing was attempted in patients with a documented infection by another test, the success rate varied according to the setting. In detail, the pooled-data analysis of 51 studies showed that H. pylori strains were isolated overall in 80.7% of 7889 patients, with success rates of 78.1%, 77.5%, 86.3%, and 86.6% before first-, second-, third-line or more therapies, respectively [ 24 ]. Therefore, the attempt to acquire information on bacterial resistance failed in more than 20% of cases, even though the infection was present.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori infection causes chronic active gastritis, peptic ulcer, and gastric mucosa-associated lymphoma. Consequently, this pathogen has been classified by the WHO as a class I carcinogen which could promote gastric cancer [ 3 ]. Infection by H. pylori was reported in the literature in both children and adults [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emergence of drug resistance represents a major challenge for eradicating this microbe despite the efficiency of the triple-management protocol followed in the empirical therapy of H. pylori infections [ 3 , 7 ]. In this respect, natural products exhibiting antimicrobial activities against such a pathogen might have a great potential for treating infections triggered by this microbe.…”
Section: Introductionmentioning
confidence: 99%